Flexible, large-area, all-solid-state supercapacitors using spray deposited PEDOT:PSS/reduced-graphene oxide. (20th April 2018) - Kumar, Neetesh; Ginting, Riski Titian; Kang, Jae-Wook
Abstract: Textile-based, flexible, all-solid-state supercapacitors are in high demand for short-term power backup and future wearable applications. Here we report a one-step spray technique to fabricate large-area flexible electrodes using poly(3, 4-ethylene dioxythiophene) polystyrene sulfonate (PEDOT:PSS), reduced graphene oxide (rGO), and carbon cloth (CC). H3 PO4 -treated CC/PEDOT:PSS and CC/PEDOT:PSS-rGO electrodes exhibit enhanced capacitance, high rate capability, and a wide voltage window (0–2.0 V). The CC/PEDOT:PSS and CC/PEDOT:PSS-rGO(20 wt%) electrodes exhibit respective specific capacitances of ∼73 and ∼170 F g −1 at 10 mV s −1, with energy and power densities of 2.6 Wh kg −1 and 2880 W kg −1 and of 11.0 Wh kg −1 and 4460 W kg −1, respectively. The device with a 25.0 cm 2 active area display capacitances of ∼6.5 and ∼5.5 F per electrode at mass loadings of 4.0 and 2.4 mg cm −2, respectively. The CC/PEDOT:PSS-rGO devices have excellent cyclic and bending stability, with capacitance retention of ∼100% after 2000 cycles and of ∼95% under bending of radius 0.5 mm. A fully charged compound device of three devices connected in series is able to power white and green LEDs. Graphical abstract: